Peningkatan Kemampuan Sosial Emosional Anak Usia 5-6 Tahun Melalui Kegiatan Bermain Kooperatif - Firawati HR; Sadaruddin Sadaruddin; Nasaruddin Nasaruddin (Ihya Ulum: Early Childhood Education Journal, 2025)
This research was motivated by the low social-emotional skills of children aged 5-6 years at TK Riffat Ummul Mukminin, which were characterized by egocentric behavior, difficulty in sharing, and unstable emotional control due to exposure to individualistic digital technology. The primary objective of this study was to improve children's social-emotional skills through the implementation of cooperative play activities. The method employed was a collaborative Classroom Action Research (CAR) following the Kemmis and McTaggart model, consisting of two cycles with stages of planning, acting, observing, and reflecting. The research subjects comprised 15 children in Group B. Data collection techniques were conducted through systematic observation, documentation, and interviews, using an observation sheet as the instrument to measure indicators of cooperation, mutual assistance, compliance with rules, and sharing ability. The results showed a significant behavioral transformation at each stage. In the pre-cycle condition, the average social-emotional skill of the children only reached 35% (Not Developed category). After the intervention in Cycle I, the percentage increased to 55.75% (Starting to Develop category). Culminating in Cycle II, the children's skills escalated dramatically, reaching a classical average of 83.75% (Very Well Developed category), thereby exceeding the established success indicator of 80%. These findings prove that cooperative play through role-playing strategies, group games, and the use of constructive media is effectively capable of reducing egocentric traits, building empathy, and training children's self-regulation optimally. The conclusion of this study confirms that cooperative play activities constitute a valid learning strategy to develop early childhood interpersonal intelligence in the school environment.